New rattans from New Guinea (Calamus, Arecaceae) - Baker, William; Dransfield, John (Phytotaxa, 2014)
The rattan genus Calamus, the largest genus of palms (Arecaceae or Palmae), is poorly known in New Guinea. In preparation for a monograph of Calamus in New Guinea, we describe and illustrate fourteen new species here: Calamus badius, C. barfodii, C. bulubabi, C. cheirophyllus, C. croftii, C. johnsii, C. lucysmithiae, C. nanduensis, C. oresbius, C. retroflexus, C. sashae, C. spanostachys, C. spiculiferus and C. womersleyi. Although many appear to be rather rare, several are widespread, common species and some are of considerable use to local people. These new discoveries highlight the need for further studies of palms in eastern Malesia, especially New Guinea.